Wujud Deiksis Sandiwara Radhio Wang Sinawang serta Relevansinya dalam Pembelajaran Bahasa Jawa SMP - Dhammayanti, Ratna Dwi; Kenfitria Diah Wijayanti; Atikah Anindyarini (Piwulang Jurnal Pendidikan Bahasa Jawa, 2024)
Deixis is a word, phrase or sentence that has a relationship between language structure and context, so deixis is important to learn, especially in learning in the form of conversations such as plays. The research aims to find out the form of deixis contained in the radio play Wang Sinawang and its relevance to Javanese language learning in junior high school. This research uses descriptive qualitative method with pragmatic approach. The data used in this study are in the form of player conversations from the transcript of the script and the data source is a document. The techniques used in data collection are document analysis techniques and interviews. The data validation technique used is the theory triangulation technique and data source triangulation. The data analysis technique was carried out using a flow analysis technique (flow model) consisting of: (1) data collection; (2) data reduction; (3) data presentation; (4) conclusion/verification. The results of the study contain the form of deixis in the play Radhio Wang Sinawang, which consists of 416 deixis persona, 208 deixis place, and 75 deixis time which are relevant to Javanese language learning KD 3.3 Examining the script of the play contained in the 2013 Curriculum for class IX junior high school. Based on the result of this research, there are 699 deixis consisting of 416 persona deixis, 208 place deixis, and 75 time deixis.